The application of calculation models for estimating primary productivity in two topical Mexican coastal lagoons - Mee, Laurence D. (Revista de Biología Tropical, 1987)
Data from detailed radiocarbon uptake studies of two turbid and highly productive Mexican tropical coastal lagoons with distinct ecological environments were used to evaluate and adapt calculation models for the integration of total daily 14C productivity (∑p). For such environments, the precision of the conventional methodology does not permit reliable estimates of Ik from the low light regions of p/I curves. Since the widely used "Talling integral" was thus not directly applicable, alternative solutions which only require knowledge of the position and height of the subsurface productivity maximum were evaluated. One of these models was found to predict ∑p to within 10% of planimetric measurements in all cases. Suggestions are given for practical application of this model and for its future development in association with the assimilation number concept.